[Translated article] Immediate-Onset Linear Effluvium Associated With High-Density Hair Transplantation: A Series of 28 Case - J.M. Mir-Bonafé; J.F. Mir-Bonafé; M. Mir-Bonafé (Elsevier, 2023)
We describe 28 patients who experienced effluvium with previously unreported features shortly after hair transplant surgery. Notable features were as follows: (a) a linear morphology; (b) immediate onset (1-3 days); (c) association with dense-pack grafting in areas of receding hairline at the temples (Mickey Mouse pattern); (d) a progressive increase in the diameter of the hair loss line (wave-like pattern); (e) in some cases, subsequent concentric linear effluvium on the crown (donut pattern); and (f) other forms of previously unreported immediate-onset effluvium. The linear morphology could be the result of dense packing, which can cause perilesional hypoxia and loss of miniaturized hairs around the recipient area. Since linear hair loss can cause patient concern about graft failure, we recommend taking images of transplanted and nontransplanted areas immediately after surgery and warning patients in advance about these transient effects, which are fully reversed in 3 months. Resumen: Describimos 28 pacientes que desarrollaron una forma de efluvio postrasplante capilar con características no descritas en la literatura: a) morfología lineal; b) aparición inmediata (uno a tres días); c) asociación con «dense packing» en entradas («signo de Mickey Mouse»); d) progresión del diámetro de la línea (patrón «wave-like»); e) posible adición posterior de efluvio lineal concéntrico a vértex («signo del donut»), y f) además de otros efluvios tampoco publicados por su inmediatez de aparición. La morfología lineal podría ser el resultado de la alta densidad colocada en nuestros pacientes, provocando hipoxia perilesional y efluvio de las unidades foliculares miniaturizadas que rodean la zona receptora. Debido a que la línea alopécica provoca inseguridad a los pacientes sobre una posible no colocación de injertos, recomendamos iconografía postoperatoria inmediata demostrando unión de áreas trasplantada y no trasplantada, así como la explicación previa al paciente de este fenómeno transitorio y completamente reversible en tres meses.